PENGEMBANGAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI SEKOLAH MENENGAH KEJURUAN NEGERI 3 MALANG - Awi Maryam (VICRATINA, 2022)
The purpose of this study is to develop and design audiovisual learning media for Islamic religious education on the topic "Wisdom of Mecca Pilgrimage in Life" at SMKN3 Malang.  The type of research used is the research and development that accompanies the development of the ADDIE model. This study explains the audiovisual development plan, develops audiovisual learning media in Hikamahaji pilgrimage materials in life, learns about the improvement of learning outcomes after using audiovisual learning media, and shows the reaction of students to audiovisual learning media. It was carried out for the purpose of seeing. The results of media validation for media professionals showed that the proportion of media was 77.1% learning feasibility in a decent category. Media verification material expert results achieved a very good category with a learning media rate of 91.4%. The effectiveness of audiovisual learning media is reflected in the rate of completion of tasks by students. The percentage of consent achieved by students is 97% in the "Very Good" category. Student response to audiovisual learning media achieves a percentage score of 85.3% in the very good category.